2006
DOI: 10.1111/j.1600-0609.2006.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine, doxorubicin, and dexamethasone or thalidomide plus dexamethasone for newly diagnosed patients with multiple myeloma?

Abstract: Multiple myeloma (MM) is a malignant plasma cell tumor that is distributed at multiple sites within the bone marrow compartments. High-dose dexamethasone regimens [including vincristine, doxorubicin, and dexamethasone (VAD) chemotherapy] induce rapid responses, and have resulted in improved survival for many patients when followed by intensive therapy with autologous stem cell support early in the disease course. However, VAD have several disadvantages including the need for an intravenous indwelling catheter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…[5][6][7] Some studies have reported the superiority of thal/dex compared with intravenous VAD based on short-term response rates. [8][9][10] In a recent randomized trial, the Eastern Cooperative Oncology Group (ECOG) found significantly higher response rates with thal/dex compared with dexamethasone alone following 4 months of therapy (63% versus 41%). 11 However, there was no data on longterm outcome measures, such as time to progression (TTP) and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Some studies have reported the superiority of thal/dex compared with intravenous VAD based on short-term response rates. [8][9][10] In a recent randomized trial, the Eastern Cooperative Oncology Group (ECOG) found significantly higher response rates with thal/dex compared with dexamethasone alone following 4 months of therapy (63% versus 41%). 11 However, there was no data on longterm outcome measures, such as time to progression (TTP) and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of renal failure in the major reported series of primary PCL is summarized in Table 1. [2][3][4][5] Plasma cell dyscrasia secreting free light chain, exclusively of g isotype, can be complicated by Fanconi syndrome. Fanconi syndrome is a generalized dysfunction of the proximal renal tubule characterized by glycosuria with normal glycemia, aminoaciduria, phosphaturia, uricosuria, and bicarbonaturia.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable results have been obtained with doxorubicin-based combination regimens [4][5][6][7][8][9][10] , such as VAD (vincristine, doxorubicin, and dexamethasone), which has response rates of 50%-80% in newly diagnosed patients and approximately 50% in patients with disease recurrence. The progression-free survival (PFS) for newly diagnosed patients treated with VAD is 9-12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increased exposure of MM patients to doxorubicin might improve response rates. Given the demonstrated effi cacy of VAD in MM patients [4][5][6][7][8][9][10] and the potential of PLD to extend the duration of bone marrow exposure to therapeutic levels of doxorubicin, a combination regimen of PLD, vincristine, and dexamethasone (DVd) could provide an advantage in the treatment of MM. We performed this study to evaluate the effi cacy and safety of the DVd regimen in the treatment of newly diagnosed MM patients in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%